Dynamics of goal characterization in students’ exams-preparation systemic activity transition processes - Mohammed-Aminu, S. (Theoretical Issues in Ergonomics Science, 2019)
This study examined the influence of students ‘goal characterization on their goal-formation processes, as characterized by their goal-classification, the systemic consideration of their activity-strategies and decision- outcomes when preparing for an examination. Using the Structural Equation Modeling approach, a functional analysis underlined by systemic principles was conducted. Firstly, the issue of whether the influence of students’ considerations of activity strategies on their decision outcomes is truly moderated by their activity goal formations, if they set highest-goals, is determined. Secondly, the issue of whether the influence of students’ considerations of activity strategies on their decision outcomes is truly mediated by their activity goal formations, if they set best-goals, is also determined. Based on the findings, the conscious goal-directed processes associated to the emergence of an individual’s thoughtfully mastered learning activity and its consequence on future design of systemic structural activity of individuals will be established.
Research Article
Keywords: Goal-oriented task; goal classification; activity goal formation; activity strategy; decision outcome